Perancangan Interior Cafe Asian Tea di Surabaya - Wiradinata, Ronald (Intra, 2015)
Cafe in Surabaya intended for tea lovers to enjoy tea after facing the daily routine - day and the pressure faced, in addition to be able to respond to their needs. Many people are less know more about tea though tea has become a quite drink in the interest of various parties, by providing a place to show the typical style of the origin of tea in Asia (Japan, Indonesia, China) in Surabaya, is expected to be a container according to the situation of communities saturating a day - day. The concept of this design is modern contemporary style, which in the process of designing blends modern concepts that are now being Boming by using a material that gives the impression of a natural with the formation of reps for meninjukkan consistency in the culture of tea-making. Of course the method of observation, brainstorming and implementation before design. Expected visitors can feel the atmosphere of the place is so into it. Therefore the design of the room is really a hallmark of the implementation of the State and tea combined with stylish modern interior, visible from the typical symbol of the State, stylized formation of the tea and the State itself.